Critical Appraisal of Guidelines for Antithrombotic Therapy in Atrial Fibrillation Post-Percutaneous Coronary Intervention - Yongqiang Fan; Gaoxing Zhang; Zhengzhipeng Zhang; Shaozhao Zhang; Menghui Lin; Yifen Lin; Yiquan Huang; Xiangbin Zhong; Xiaodong Zhuang; Xinxue Liao (Ubiquity Press, 2022)
Objective: In our present study, our objective was to appraise guidelines on antithrombotic therapy in atrial fibrillation post-percutaneous coronary intervention and to explore the differences in treatment practices for better informed decision-making. Methods: We searched for English language guidelines published between January 2000 and December 2020 at MEDLINE, Embase and websites of guideline organizations. Guidelines with recommendations on antithrombotic regimens for patients with AF undergoing PCI were included. Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument was applied to assess guidelines. The reporting of conflicts of interest (COI) was evaluated separately by the RIGHT (Reporting Item for Practice Guidelines in Healthcare) checklist as supplementary items. Results: Sixteen guidelines were included, among which 13 (81.25%) were considered as 'recommended' and 1 (6.25%) as 'unrecommended.' The average scores of guidelines ranged from 55% to 88% (<60% as low quality, 60-70% as sufficient quality, and >70% as good quality). Among the 6 domains of AGREE II, scope and purpose (84%) and editorial independence(87%) were considered to be the fields in which CPGs performed best, evidenced by the highest mean AGREE II scores. The domains in which the reviewed CPGs received the lowest mean scores were stakeholder involvement (63%) and applicability (58%). The intraclass correlation coefficient scores were excellent in each domain. The overall quality of the selected CPGs was optimal, with the highest score in domain 'scope and purpose', and the lowest score in the domain 'applicability.' The reporting of COI was satisfactory. Conclusions: For the recommendations on antithrombotic strategies, guidelines with high AGREE II scores still exist discrepancy on the timing and selection. Current guidance documents on the treatment vary in methodological rigor and recommendations are not always consistent.